Типы гемоглобина, трансферрина, преальбумина и содержание калия в крови карпов из рыбхоза «Волма» (БССР) - Балахнин, И. А.; Богданов, Л.В.; Лазовский, А.А. (Вестник зоологии, 1973)
Haemoglobin, transferrine, prealbumin systems and blood potassium content were investigated in carp from fishery farm IVOlina), the Byelorussian SSR. Monomorphism of heterogenic system of haemoglobins and polymorphism of transferrines are shown. The transferrine system is controlled by six allels and is in genic equilibrium. Two systems of prealbumins are detected in the same carps: Pa I and Pa II, one of which -- Pa II is polymorphous and is presented by three types: A, B and AB.
Individuals of two types are found by the method of flame photometry: with high and low potassium content in blood. A hypothesis is advanced on genetic nature of the found polymorphism, the necessity of potassium content determination in blood of thoroughbred carps and common carps as well as expediency of family analysis are empha¬sized.